Assessing hand motor function in chronic immune-mediated neuropathies: a proof-of-concept study using a data glove - Elisa Gilliam; Pascal Achenbach; Gernot J. Suemmermann; Manuel N. Wessely; Peter Rossmanith; Maike F. Dohrn; Jörg B. Schulz; Anne Waschbisch; Robert Brunkhorst (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Chronic immune-mediated neuropathies are clinically heterogeneous and require regular, objective, and multidimensional monitoring to individualize treatment. However, established outcome measures are insufficient regarding measurement quality criteria (e.g., reliability, objectivity) or functional relevance. Wearables such as data gloves might be helpful, allowing repeated quantification of complex everyday life-relevant motor function of the hand. Methods 25 patients with chronic inflammatory demyelinating polyneuropathy or multifocal motor neuropathy were followed-up at five time points during maintenance therapy with intravenous immunoglobulin. 14 of them showed clinically relevant hand motor impairment. We examined the patients’ hand function using a data glove which quantifies the active range of motion (ROM) of the hand based on three different movement patterns. In addition, clinical outcome parameters (grip strength measurement, MRC Sum Score, INCAT disability score), nerve conduction studies (NCS), and high-resolution ultrasound (HRUS) were performed, and patient-reported outcome measures (PROMs) like the Rasch-built Overall Disability Scale (R-ODS) were assessed. We calculated correlation coefficients, performed Receiver Operating Characteristic analysis, as well as correlation analyses for the glove data and clinical outcome parameters. Longitudinal analyses were based on a Linear Mixed Model, and we assessed construct validity of the data glove by analyzing correlations between the glove measurements and well-established clinical parameters. Results We found good to excellent test–retest reliability for the ROM in all glove movement patterns (Intraclass correlation coefficients = 0.83–0.94), underlining the ability to capture clinical stability. Moreover, the glove demonstrated adequate, sensitivity and specificity in detecting hand motor impairment (area under the curve (AUC): 0.714–0.780), and it performed better than NCS and HRUS (AUC: 0.552/0.701). The AUC values for the metrically scaled parameters include: Vigorimeter (AUC: 0.929) and R-ODS (AUC: 0.698). Additionally, the data glove proved to be a valid tool, as we demonstrated moderate to strong, significant correlations between the glove and established clinical parameters (especially Vigorimeter), as well as PROMs (especially R-ODS). Conclusions This data glove allowed for a non-invasive assessment of the hand motor function and yielded investigator-independent results that reliably reflected individual functional deficits with relevance to everyday life. Future studies should explore the ability to predict clinically meaningful responses to immunomodulatory treatment and to support and monitor rehabilitation progress, with potential applications in other neurological diseases as well. Trial registration at the German Clinical Trials Register, Deutsches Register Klinischer Studien (DRKS: 00027345), retrospectively registered on 23rd March 2022: https://drks.de/search/de/trial/DRKS00027345